Primary Idiopathic Congenital Lymphedema Presenting as Swelling of Dorsum of Both Feet – A Case Report - Hasan, Tanjida; Nasreen, Faria; Rahman, Mahbub ur (Bangladesh Journal of Nuclear Medicine, 2022)
Lymphedema is a debilitating, progressive disease causing major healthcare problem. This condition is broadly classified as primary and secondary lymphedema. Congenital subtype is a rare form of primary lymphedema. Proper history taking and appropriate investigations can rule out the other differentials of lymphedema. Early diagnosis is essential for early treatment which may halt the progression and alleviate symptoms. Lymphoscintigraphy is an important but simple imaging modality which helps to diagnose and grade lymphedema initially as well as in follow up. An interesting case of primary idiopathic congenital lymphedema presenting with dorsum of feet swellings is reported here highlighting the importance of lymphoscintigraphy. Bangladesh J. Nuclear Med. 25(1): 41-44, 2022